Particulate size of microalgal biomass affects hydrolysate properties and bioethanol concentration - Harun, Mohd Razif; Danquah, Michael Kobina; Thiruvenkadam, Selvakumar (Hindawi Publishing Corporation, 2014)
Effective optimization of microalgae-to-bioethanol process systems hinges on an in-depth characterization of key process parameters relevant to the overall bioprocess engineering. One of the such important variables is the biomass particle size distribution and the effects on saccharification levels and bioethanol titres. This study examined the effects of three different microalgal biomass particle size ranges, 35 μm ≤ ≤ 90 μm, 125 μm ≤ ≤ 180 μm, and 295 μm ≤ ≤ 425 μm, on the degree of enzymatic hydrolysis and bioethanol production. Two scenarios were investigated: single enzyme hydrolysis (cellulase) and double enzyme hydrolysis (cellulase and cellobiase). The glucose yield from biomass in the smallest particle size range (35 μm ≤ ≤ 90 μm) was the highest, 134.73 mg glucose/g algae, while the yield from biomass in the larger particle size range (295 μm ≤ ≤ 425 μm) was 75.45 mg glucose/g algae. A similar trend was observed for bioethanol yield, with the highest yield of 0.47 g EtOH/g glucose obtained from biomass in the smallest particle size range. The results have shown that the microalgal biomass particle size has a significant effect on enzymatic hydrolysis and bioethanol yield.